Nanoemulsified adlay bran oil reduces tyrosinase activity and melanin synthesis in B16F10 cells and zebrafish. Issue 10 (5th September 2019) - Ting, Yuwen; Hu, Yin‐Ting; Hu, Jing‐Yu; Chang, Wen‐Chang; Huang, Qingrong; Hsieh, Shu‐Chen
Abstract: The efficacy of oily components is often difficult to evaluate due to their incompatibility with most models. Here, we emulsified adlay bran oil (ABO), processed it to a nanoscale, and investigated its anti‐hyperpigmentation efficacy, assessed for its inhibitory effects against tyrosinase activity and melanin production, in an in vitro system (mouse melanoma B16F10 cells) and an in vivo system (zebrafish embryos). ABO induced dose‐dependent reductions in tyrosinase activity and melanin production in both the melanoma cells and zebrafish, without affecting viability. The efficacy of ABO was strongly influenced by emulsion particle size in the zebrafish but not in the cells. These results indicate that ABO has potential as a tyrosinase inhibitor and anti‐hyperpigmentation agent and that the emulsion system is an effective method for delivering the bioactive components of ABO to living systems that could be utilized for other oily components. Abstract : The by‐product from adlay processing was used as the source of functional food ingredient. Nanoemulsion was developed for oral delivery of adlay bran oil and was effective to inhibit tyrosinase activity and melanin synthesis as shown in the in vitro B16F10 cells model and in vivo zebrafish were used in the study.